2016
DOI: 10.1021/acs.analchem.6b02640
|View full text |Cite
|
Sign up to set email alerts
|

UV–Visible Spectroscopy-Based Quantification of Unlabeled DNA Bound to Gold Nanoparticles

Abstract: DNA-functionalized gold nanoparticles have been increasingly applied as sensitive and selective analytical probes and biosensors. The DNA ligands bound to a nanoparticle dictate its reactivity, making it essential to know the type and number of DNA strands bound to the nanoparticle surface. Existing methods used to determine the number of DNA strands per gold nanoparticle (AuNP) require that the sequences be fluorophore-labeled, which may affect the DNA surface coverage and reactivity of the nanoparticle and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…The spectra (Fig. S2B) showed that the AuNPs were stabilized by the negatively charged DNA that acted as electrostatic repulsing capping agent among the AuNPs as reported in the literature (Baldock and Hutchison, 2016;Xu et al, 2016). Moreover, the nanoparticles functionalization with hpDNA was confirmed by the presence of a sharp peak at 260 nm indicating the presence of DNA.…”
Section: Aunps-dna Functionalization and Qcm Sensors Modificationsupporting
confidence: 71%
“…The spectra (Fig. S2B) showed that the AuNPs were stabilized by the negatively charged DNA that acted as electrostatic repulsing capping agent among the AuNPs as reported in the literature (Baldock and Hutchison, 2016;Xu et al, 2016). Moreover, the nanoparticles functionalization with hpDNA was confirmed by the presence of a sharp peak at 260 nm indicating the presence of DNA.…”
Section: Aunps-dna Functionalization and Qcm Sensors Modificationsupporting
confidence: 71%
“…Then the AuNP conjugates are dissolved by NaCN to release FITC-labelled IgG [30,31] which is subsequently assayed using spectrofluorimetry. This direct method is benchmarked against two indirect methods that rely on assay of excess FITC-labelled IgG in the supernatant using spectrofluorimetry or sandwich ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of mixing of PPy and DNA in PPy/ DNA was evaluated in this work by UV-vis absorption spectroscopy. As shown in Figure 2, a π → π* transition is likely to occurs in the pyrrole ring present in the pyrrole-alginate conjugate, allowing quantification of the amount of PPy/DNA by UV-vis absorption spectroscopy at 217 nm [17]. The result is similar to other researcher's findings in which they suggested that, the changed π -bond chromophore of indene/pyrrole aromatic ring system in ClnPy nanomaterial is due to overlapping of phenyl π -conjugated unit and skeleton of pyrrole monomer and is possibly responsible for the blue shifted and broadened absorption peak.…”
Section: Uv-vis Characterisation Of Ppy/dnamentioning
confidence: 99%